The new digital sales enablers - Cantù, Chiara; Martinelli, Elisa Martina (Piccola Impresa / Small Business, 2023)
Purpose: The global health emergency situation in 2020 has asked some companies to review the business model in a context characterized by a strong digital transformation. On this innovative drive, new digital players able to support the digital transformation of companies have emerged. This process is particularly relevant in Italy, where SMEs operating in B2B are increasingly approaching these technological solutions. The aim of the paper is therefore to understand what the main characteristics of the business model of the new B2B digital players are and what have been the main changes considering the crisis driven innovation perspective. Design/methodology/approach: The methodology used in this study is based on a constructive multiple case research design. Practical and Social implications: New digital actors are relevant for SMEs as they support companies in developing a digital strategy, coordinating the use of different platforms including marketplaces, to identify new customers or strengthen relationships with acquired customers. The combination of all these solutions leads to an increase in the global presence of the players belonging to the network, providing an international showcase. The new solutions proposed by digital players are data driven and the potential of technology can only be fully utilized by adopting a holistic approach, considering the possibility of co-creating value. Originality of the study: Through the research, new digital players identified in digital sales enablers emerge. These actors support the digital transformation process of a company and its activities in a national and international context, providing and implementing their digital strategy.